Análise das múltiplas variáveis relacionadas com o doador de órgãos cadáver e os processos de captação e isolamento de ilhotas pancreáticas - Sá, Gustavo Pilotto Domingues [UNIFESP] (2009)
The shortage of cadaveric organ donors relative to demand and the prioritization for donation for the whole organ pancreas transplantation became obstacles to obtaining organs for isolation of pancreatic islets both for research and islet transplantation. Few studies have evaluated whether there are characteristics related to donors and some stages of the isolation that can be risk factors for a better isolation of pancreatic islets. Objective: To analyze the relationship between the multiple variables related to the donor and the process of recovery / isolation of islets with the total number of equivalent isolated pancreatic islets (IEq). Method: We analyzed several variables in 74 islets isolations in relation to the outcome of IEq isolated at the end of the process: age, sex, BMI, ICU stay, use of drugs, smoking, hypertension, diabetes in 1st degree relatives, blood type, glucose, urea, creatinine, ALT, AST, amylase, pancreatic weight, appearance of the pancreas during the recovery, ischemia duration and lot of enzyme used in the pancreas digestion. Results: In univariate analysis, BMI (p <0.01) and macrospcopic appearance of the pancreas during the capture (p = 0.04) were the variables related to a greater number of IEqs. For the multivariate analysis, the only variable that showed statistical significance was the BMI (p = 0.0003). Through the establishment of an ROC curve, BMI = 30 appeared as a cutoff point where the pancreas of donors with BMI > 30 generate more islets than donors with a BMI < 30 (p <0.001). Conclusion: The BMI of cadaveric pancreas donor is presented as the only variable statistically significant. The donor with a BMI> 30 is more likely to provide better isolation of pancreatic islets.